Dielectric tuned circular dichroism of L-shaped plasmonic metasurface. (21st November 2017) - Qu, Yu; Zhang, Zhidong; Fu, Tong; Wang, Gang; Wang, Tiankun; Wang, Mingyan; Bai, Yu; Zhang, Zhongyue
Abstract: In this paper, a dielectric layer is introduced to tune circular dichroism (CD) of chiral plasmonic metasurfaces. The dielectric layer is used to control the optical phase of electric diploes in Born–Kuhn configurations. To prove our assumption, an L-shaped plasmonic metasurface consisting of two metallic slices is prepared by glancing angle deposition, and then an SiO2 slice is deposited on one arm of the L-shaped metasurface. Experimental results reveal that CD of the L-shaped plasmonic metasurface can be tuned by the thickness of the SiO2 slice. These findings not only contribute to a better understanding of the CD physical mechanism, but also can be used in nanophotonic metasurfaces because of the concise fabrication process.